Optimal Body Masses for Different Olympic Sports - Igor Kudybyn; Igor Nesteruk; Sergei Pereverzyev; Alberto Redaelli; Bohdan Shepetyuk; Оleg Chertov (Innovative Biosystems and Bioengineering, 2018)
Background. The weight of the best athletes at different distances and in different sports can be very different. It is known that rowers, as a rule, are very massive. In order to give a chance to athletes with a small mass, the rowing federation was introduced a special category with the weight restrictions. These facts are connected with the peculiarities of the aerobic and un-aerobic activities, drag and propulsion characteristics.